Caring for Children With Medical Complexity: A Clinical, Patient-Focused Curriculum - Brittany Lattanza; Divya Lakhaney; Theresa Scott; Ashley Croker-Benn; Mirna Giordano; Sumeet L. Banker (Association of American Medical Colleges, 2024)
Introduction Caring for children with medical complexity (CMC) requires specialized knowledge and skills. However, no standardized curricula are used across training programs as institutions have varying needs and resources. Methods We created a patient-focused, interactive curriculum for two CMC topics: feeding/nutrition and pain/irritability. We integrated the 45-minute sessions into morning protected patient-care time on an inpatient pediatric team at an urban tertiary care hospital. Targeted toward all pediatric residents and medical students rotating in inpatient pediatrics over a 12-month period, the sessions used a mix of didactic, discussion, and hands-on activities. Learners on one of two inpatient teams received the curriculum, while those on the other received a curriculum unrelated to CMC and served as a control group. Both groups completed retrospective pre/post self-assessments to evaluate self-efficacy with respect to the learning objectives. Results Over the 12-month period, 72 surveys were completed for the feeding/nutrition session, 78 surveys for the pain/irritability session, and 42 control surveys. The intervention group saw the greatest increase in self-efficacy scores generally in the feeding/nutrition session. All eight learning objectives saw significant improvement in self-efficacy scores for the intervention group. There was significantly greater improvement in self-efficacy for the intervention group compared to the control for all eight learning objectives. Discussion Through this patient-focused curriculum, learners had improved self-efficacy scores compared to the natural learning occurring on the inpatient service. The curriculum could be adapted to fit the needs of other institutions and provides a practical, hands-on approach to learning about caring for CMC.